Pelatihan Penggunaan Google Meet dan Google Classroom bagi Dosen Tidak Tetap Universitas Kristen Wira Wacana Sumba - Mayun Erawati Nggaba; Erwin Randjawali; Yuliana Tamu Ina Nuhamara; Anggriati Ledu Ngaba; Mega Retno Wulandari; Darius Imanuel Wadu; Itha Priyastiti; Elsy S H Taunu; Stevvileny Angu Bima; Iona Lisa Ndakularak; Yuliana S Eko; Irna Natalis Sanit (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Universitas Kristen Wira Wacana Sumba is one of the universities that organizes online learning. This happened as a result of the COVID-19 pandemic. This situation requires all lecturers to be able to conduct online learning by utilizing the available facilities, namely Google Classroom and Google Meet, both permanent and adjunct lecturers. Permanent lecturers have used the application since the beginning of the covid-19 pandemic, while adjunct lecturers who held lessons this semester have never used the Google Classroom and Google Meet applications. If this is allowed, then learning will not be held properly. Therefore, this training is carried out in several stages, namely analyzing the needs of non-permanent lecturers, implementing activities, and following up. This training makes the online learning by adjunct lecturers can be carried out properly. Based on the results of the follow-up, the participants proposed further training on the use of Google Classroom, especially in making assignment assessment rubrics and quizzes.